Minimally Invasive Repair of Morgagni Hernia - A Multicenter Case Series - Lamas-Pinheiro, R (2016)
Children may benefit from minimally invasive surgery (MIS) in the correction of Morgagni hernia (MH). The present study aims to evaluate the outcome of MIS through a multicenter study. National institutions that use MIS in the treatment of MH were included. Demographic, clinical and operative data were analyzed. Thirteen patients with MH (6 males) were operated using similar MIS technique (percutaneous stitches) at a mean age of 22.2±18.3 months. Six patients had chromosomopathies (46%), five with Down syndrome (39%). Respiratory complaints were the most common presentation (54%). Surgery lasted 95±23min. In none of the patients was the hernia sac removed; prosthesis was never used. In the immediate post-operative period, 4 patients (36%) were admitted to intensive care unit (all with Down syndrome); all patients started enteral feeds within the first 24h. With a mean follow-up of 56±16.6 months, there were two recurrences (18%) at the same institution, one of which was repaired with an absorbable suture; both with Down syndrome. The application of MIS in the MH repair is effective even in the presence of comorbidities such as Down syndrome; the latter influences the immediate postoperative recovery and possibly the recurrence rate. Removal of hernia sac does not seem necessary. Non-absorbable sutures may be more appropriate.